PERCEPTIONS ON PLAGIARISM AND THE IMPLICATIONS FOR TEACHING AND LEARNING STRATEGIES AT AN EMI UNIVERSITY IN INDONESIA - Fitria, Risa (Jurnal Smart, 2020)
This study tries to answer two questions, namely 1) What do the lecturers and the students perceive about the practice of plagiarism in L2 writing? 2) What strategies did the lecturers and the students apply to writing L2 to avoid plagiarism? This study aimed at investigating the views of lecturers and students on plagiarism and its implications for teaching and learning at one of the EMI universities in Indonesia. The findings showed that both lecturers and students had negative views towards plagiarism. However, even though plagiarism was considered as an unacceptable behavior, the students would be likely to commit plagiarism under certain circumstances. Back translation was also found to be the most common strategy that the students used to avoid plagiarism. The study finally recommended higher education institutions to equip students with necessary language and writing skills needed in academic settings as early as possible in order for them to avoid plagiarism.